Hydrogenation of carbon dioxide to formate by α-diimine RuII, RhIII, IrIII complexes as catalyst precursors - Makuve, Nyasha; Mehlana, Gift; Tia, Richard; Darkwa, James; Makhubela, Banothile C.E. (Elsevier B.V., 2021)
The conversion of CO2 into valuable chemicals has been of major interest because it is cheap and readily available. The concept of reducing CO2 pollution via its utilization into valuable products has inspired us to synthesise novel 4,4'-((1Z)-butane-2,3-diylidenebis(azanylylidene))dibenzoic acid (L) metal complexes {[(L)RuII] (C1), [(L)RhIII] (C2), [(L]IrIII (C3)} complexes for catalytic hydrogenation of CO2. The α-diimine metal complexes (C1–C3) were characterised using several analytical techniques, including: NMR spectroscopy and single crystal X-ray crystallography. In a mixture of THF/H2O and a base, all three catalyst precursors were able to hydrogenate CO2 cleanly to formate as a product. However, the best combination of catalyst precursor and a base was C1 and DBU that selectively produced formate at a moderate temperature of 120 °C and at 60 bar. The best productivity under these conditions is TOF of 35 h−1 within 2 h and a TON of 322. This work is significant because it provides a one-step synthesis for formate from CO2 using α-diimine-based complexes which can be synthesised in a one-step reaction. The density functional theory calculations on C1 supports that Ru–H is the active species in the process of CO2 hydrogenation to formate with the insertion of the CO2 to Ru–H being the rate determining step.